An Industrial systems study on Marton Manufacturing Philippines, Inc. - Olfindo, Vanessa; Peraz, Melanie; Pinili, Dominic; Uy, Marie Hazeline (College of Engineering, 2002)
Marton is presently suffering from economic slowdown. The production is lean such that the sales in the year 2002 is only 18.41% of the best operating level. This study then recommends necessary plans to the Marton management which would support regrowth strategies, stabilization or continuous improvement of the system. The researchers generated and evaluated aggregate and capacity plans that targets the projected demand level for Marton products. After the evaluation, the recommendation of the group is to endeavor on a regrowth of six years, then improve the system through continuous expansion using the necessary requirements suggested in the aggregate plan of a chase strategy, and capacity plans.